Physical characterization of used lubricating oil as fuel production feedstock - Furqon Zami; Anggoro Didi D.; Sutanto Heri (E3S Web of Conferences)
These articles aim to identify the physical characteristics of the hydrocarbons in used lubricating oil, which is required as feedstock for process designs, and to address certain issues with the equipment used in the catalytic cracking process in the future. The data can be used to determine specific parameters to refine used lubricating oil into fuel. Used lubricating oil falls into the medium-heavy oil category based on the results of the characteristic tests. The physical test findings determined the sample’s fluidity and volatility qualities such as the ASTM D 92 flash point, ASTM D 97 pour point, ASTM D 4052 specific gravity test, ASTM D 1160 distillation, and ASTM D 445 viscosity. Based on test results, the following values were found: initial boiling point: 160°C, flash point: 198°C, specific gravity (60°F): 0.864, viscosity (100°C): 34.9 Centi Stoke, and pour point: > -30oC. Based on the collected data, the KUOP value is more than 12.5 where the value shows paraffinic hydrocarbon type and the API gravity value is 32.3.